Pengembangan Model Wirausaha di Lembaga Pendidikan Dasar/ Menengah/Tinggi - Maratul Isnaini; Novita Ananda Srianto; Wiranda (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to examine the development of entrepreneurship models at elementary, secondary, and tertiary levels in order to improve students' entrepreneurial skills. This study uses a literature study approach by reviewing various scientific sources such as journal articles, books, and relevant research reports. Data are analyzed descriptively and qualitatively through a process of collection, reduction, and interpretation of findings to obtain a comprehensive picture of the implementation of entrepreneurship education at various levels of education. The results indicate that the development of entrepreneurship models needs to be adapted to the developmental characteristics of students at each level. In elementary education, entrepreneurship learning is more effectively delivered through simple activities that instill basic values ​​such as discipline, responsibility, creativity, and independence. At the secondary level, students are directed to entrepreneurial practices through activities such as school bazaars, student cooperatives, and simple business projects that train basic managerial skills. Meanwhile, in higher education, entrepreneurship models emphasize direct practice, startup business development, and collaboration with the industrial world. Thus, structured and tiered entrepreneurship education can be an effective strategy in developing a creative, independent, and competitive generation in the field of entrepreneurship.